The Denial of Emergency Protection: Factors Associated with Court Decision Making - Duckett-Pritchard, Danielle (2008)
Despite the importance of civil orders of protection as a legal resource for victims of intimate partner violence, research is limited in this area, and most studies focus on the process following a court’s initial issuance of an emergency order. The purpose of this study is to address a major gap in the literature by examining cases where victims of intimate partner violence are denied access to temporary orders of protection. The study sample included a review of 2,205 petitions that had been denied by a Kentucky court during the 2003 fiscal year. The study offers important insights into the characteristics of petitioners and respondents to denied orders and outlines individual, contextual, structural, qualitative/perceptual, and procedural factors associated with the denial of temporary or emergency protective orders. Recommendations for statutory changes, judicial education, and future research to remedy barriers to protection are offered